VX-765 inhibits pyroptosis and reduces inflammation to prevent acute liver failure by upregulating PPARα expression - Jiao, Mingjing; Wang, Jiachao; Liu, Wenpeng; Zhao, Xin; Qin, Yanjun; Zhang, Chunhuan; Yin, Hongzhu; Zhao, Caiyan (Annals of hepatology, 2023)
As a fatal clinical syndrome, acute liver failure (ALF) is characterized by overwhelming liver inflammation and hepatic cell death. Finding new therapeutic methods has been a challenge in ALF research. VX-765 is a known pyroptosis inhibitor and has been reported to prevent damage in a variety of diseases by reducing inflammation. However, the role of VX-765 in ALF is still unclear. ALF model mice were treated with D-galactosamine (D-GalN) and lipopolysaccharide (LPS). LO2 cells were stimulated with LPS. Thirty subjects were enrolled in clinical experiments. The levels of inflammatory cytokines, pyroptosis-associated proteins and peroxisome proliferator-activated receptor α (PPARα) were detected using quantitative reverse transcription-polymerase chain reaction (qRT‒PCR), western blotting and immunohistochemistry. An automatic biochemical analyzer was used to determine the serum aminotransferase enzyme levels. Hematoxylin and eosin (HE) staining was used to observe the pathological features of the liver. With the progression of ALF, the expression levels of interleukin (IL) -1β, IL-18, caspase-1, and serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were increased. VX-765 could reduce the mortality rate of ALF mice, relieve liver pathological damage, and reduce inflammatory responses to protect against ALF. Further experiments showed that VX-765 could protect against ALF through PPARα, and this protective effect against ALF was reduced in the context of PPARα inhibition. As ALF progresses, inflammatory responses and pyroptosis deteriorate gradually. VX-765 can inhibit pyroptosis and reduce inflammatory responses to protect against ALF by upregulating PPARα expression, thus providing a possible therapeutic strategy for ALF.